Roles and Functions of Nursing Management in Strengthening the Healthy Nurse Program for Nurses at Hospital - Rio Verdiansyah; Rr. Tutik Sri Hariyati; Tuti Afriani; Hanny Handiyani; Krisna Yetti (Indonesian Journal of Global Health Research, 2025)
Nurse well-being is a critical foundation for ensuring the quality of healthcare services. However, the high prevalence of physical fatigue, occupational stress, and biopsychosocial-spiritual (BPSS) imbalances among nurses indicates an urgent need for strategic interventions rooted in nursing management. This residency project aimed to develop and implement the Healthy Nurse Program as an innovative initiative to holistically enhance nurse well-being at X Hospital. The program adopted Kurt Lewin’s planned change theory, encompassing the stages of unfreezing, changing, and refreezing. Implementation began with problem identification through interviews, observations, and BPSS-based questionnaires, followed by the formulation of a Plan of Action, socialization, and interventions such as workplace stretching, ergonomic education, MBCA monitoring, and spiritual reflection sessions.The study involved 32 newly hired nurses (≤1 year experience) selected through purposive sampling, with data analyzed using a fishbone diagram. Initial evaluation revealed a high prevalence of muscle fatigue, work-related stress, and over-fat conditions among nurses, along with strong support for program implementation. The Healthy Nurse initiative strengthened core nursing management functions and fostered a culture of sustainable workplace wellness. These findings provide a critical foundation for integrating occupational health promotion into hospital systems based on evidence-based practice.